Strengthening the Competitive Advantage of Commissioning : Case study on a complex global project-based environment - Edsvik, Cecilia (My University, 2020)
Today’s global business environment has become increasingly complex due to rapid technological innovation, changing business models and customer requirements. In a project-based environment, commissioning is the phase where a company’s ability to combine its organization’s competence into competitive project execution is crystallized. Yet, organizations fall short in integrating commissioning planning into the project life cycle whereas commissioning often becomes reactive by nature and end up in cost overrun. The objective of this thesis is to describe how a company’s competitive advantage can be strengthened through improving its project commissioning process. An answer to this is looked for in theory related to competitiveness, organizing of firm resources in a project-based environment, project management as well as previous research on commissioning. The empirical part of the thesis aims for understanding the internal processes contributing to competitive commissioning in case company context and give suggestions on how these can be improved. The research was conducted as a qualitative case study and data was gathered through study of secondary data and interviews and discussions with stakeholders involved in commissioning activities of the case organization. The study identified the key factors considered critical to successful commissioning of the case product, most of them congruent with success factors found in literature. Among these the main development area was found to be in transferring of technical knowledge from project to commissioning. Using elements of action research, a framework for commissioning documentation for the case product and a proposal for responsibilities of documentation was developed. Strongly connected to theory, the framework provides a valuable base for further implementations within the case company. It was recognized that the complexity and variance of the project scope, as well as integration with connected products, impose challenges for standardization of processes and documentation. It is however imposed that the gains of adapting a proactive approach to commissioning will win the coordination efforts related to it. Integrating technical planning of commissioning into earlier stages of a project life cycle enable early identification of criticalities, result in increased commissioning accuracy, cost reduction and better utilization of resources. Long term benefits of this is the natural inclusion of a commissioning thinking in both project life cycle and product design that might increase both budgetary and technical accuracy. Ultimately, a more efficiently executed commissioning contribute to customer satisfaction and the competitiveness of project delivery.
Keywords: competitive advantage; project management; dynamic capabilities; marine industry; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management